PENGARUH TERAPI MUROTTAL QUR’AN TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF DI BIDAN PRAKTIK MANDIRI (BPM) ERNITA KOTA PEKANBARU TAHUN 2017 - Fatiyani Alyensi; Hafsah Arifin (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
As a physiological state in labor, pain causes discomfort due to stimulation at certain nerve endings. One of ways considered to eliviate the pain is by listening to Qur'an recital (murottal). This therapy stimulates delta waves which make the listener more relax, peaceful, and comfortable so that hypopfise and hypothalamus produce β-endorphin as natural analgesic This research aimed to determine the influence of Qur'an recital therapy to the intensity of labor pain during the first stage in the active phase. This was a quasi experimental research with a pre-test post-test group design conducted from February to July 2017 at BPM (privately practising midwife) Ernita of Pekanbaru. The subjects were 20 mothers with normal delivery taken with purposive sampling technique. The data were collected by pain measurement method before and after the Qur'an recital treatment 30 minutes with the combined pain scale of Verbal Description Scale (VDS), Comparative Pain Scale and Wong Baker Pain Rating Scale. Data processing is computerized with dependent t-test (α = 0.05). The results showed that the mean intensity of labor pain before the treatment was 6.75 and after the treatment was 4.80. The data analysis showed that there was a difference in the intensity of labor pain in the active phase before and after being given the treatment (p = 0,000). It is recommended to BPM Ernita to disseminate the Qur'an recital therapy as one of the non-pharmacologic pain reduction methods in childbirth so that it can be a procedure as an effective method in reducing labor pain.